Psychometric Properties of Pain Catastrophizing Scale in Patients with Carpometacarpal Osteoarthritis of Thumb—Item Response Theory Analysis - Suomela, Sara; Saltychev, Mikhail; Juhola, Juhani; Taskinen, Hanna-Stiina (MDPI AG, 2026)
Objectives: The aim of this study was to evaluate the psychometric properties of the Pain Catastrophizing Scale (PCS) in patients with carpometacarpal osteoarthritis of the thumb.
Methods: In this cross-sectional register-based study of 253 patients with carpometacarpal osteoarthritis of the thumb, a two-parameter item response theory analysis was used to evaluate the items’ difficulty and discrimination parameters.
Results: Of 253 patients, 245 (57%) were women. The mean age was 56.0 (SD 16.5) years. The mean total PCS score was 14.0 (SD 10.5) points. Difficulty estimates were distributed fairly evenly across the item score scale, with a slight shift towards higher scores. Discrimination of both total and subscale scores was perfect, varying from 1.91 to 2.84.
Conclusions: PCS was able to discriminate well between different levels of catastrophizing. PCS performed slightly more accurately when the catastrophizing level was above average in the studied sample. PCS can be recommended for clinical use when assessing catastrophizing in patients with carpometacarpal osteoarthritis of the thumb.